Storage of the vital metal tungsten in a dominant SCFA-producing human gut microbe Eubacterium limosum and implications for other gut microbes - Nana Shao; Dayong Zhou; Gerrit J. Schut; Farris L. Poole; Sydney B. Coffey; Aaron P. Donaghy; Saisuki Putumbaka; Michael P. Thorgersen; Lirong Chen; John Rose; Bi-Cheng Wang; Michael W. W. Adams (mBio)
ABSTRACT Enzymes containing tungsten rather than the ubiquitous and analogous element molybdenum are prevalent in the human gut microbiome, especifically in microbes that contribute to overall gut health. Eubacterium limosum is a dominant human gut organism whose production of beneficial short-chain fatty acids (SCFAs) from lactate involves tungstoenzymes. Here, we characterized E. limosum Tub, a tungsten storage protein. Tub has a sub-nanomolar affinity for tungstate and contains a single TOBE domain first characterized in a molybdate storage protein. Crystal structures revealed Tub assembles as a hexamer composed of a trimer of dimers, capable of binding eight tungstate oxyanions at two distinct binding sites located at inter-subunit interfaces. Tungstate-saturated Tub exhibited unusually high thermal and chemical stability. Glucose-grown E. limosum accumulates tungsten in Tub and has low levels of two tungstoenzymes, termed WOR1 and FDH, which oxidize aldehydes and formate, respectively. Lactate-grown cells contain high concentrations of these two tungstoenzymes where WOR1 and FDH are involved in converting lactate to SCFAs. Glucose-grown cells appear to accumulate tungstate in Tub in preparation for lactate availability in the human gut. Tub and other TOBE-containing proteins are widespread in the human gut microbiome, and gene co-occurrence analysis predicts that there are comparable numbers of TOBE-containing proteins involved in the storage of tungstate as there are that bind molybdate. The results with E. limosum represent an important step for understanding tungsten storage mechanisms for tungstoenzymes within human gut microbes in general.IMPORTANCETungsten metabolism was found to be prevalent in the human gut microbiome, which is involved in the detoxification of food and antimicrobial aldehydes, as well as in the production of beneficial SCFAs. In this study, we characterized a protein in the human gut microbe, Eubacterium limosum, that stores tungstate in preparation for its use in enzymes involved in SCFA generation. This revealed several families of tungstate binding proteins that are also involved in tungstate transport and tungstate-dependent regulation and are widely distributed in the human gut microbiome. Elucidating how tungsten is stored and transported in the human gut microbes contributes to our understanding of the human gut microbiome and its impact on human health.